Market vs. Residence Principle: Experimental Evidence on the Effects of a Financial Transaction Tax - Jürgen Huber; Michael Kirchler; Daniel Kleinlercher; Matthias Sutter (Institute for the Study of Labor (IZA), 2014)
While politically attractive in order to generate tax revenues, the effects of a financial transaction tax (FTT) are scientifically disputed, not the least because seemingly small details of its implementation may matter a lot. In this paper, we provide experimental evidence on the different effects of a FTT, depending on whether it is implemented as a tax on markets, on residents, or a combination of both. We find that the effects of a tax on markets are different from a tax on residents, with negative effects of a market tax on volatility and trading volume. The residence principle shows none of these undesired effects. In addition to studying aggregate market outcomes, we investigate how individual traders react to different forms of a FTT and whether their risk attitude is related to these reactions. We find no such relationship, meaning that a FTT affects traders with different risk tolerances similarly.
Keywords: C91; G10; E62; 330; Financial Transaction Tax; experimental finance; residence principle; market principle